Dinamic Capital Structure Of Firms In Indonesia Stock Exchange - Arni Surwanti (Tamkang University, 2012)
This study attempted to examine the dynamic capital struclure model bas€d on a sample on manutbcturing company ilt lndonesia. The dala used h panel data of listed companies in Indonesia Stock Erchange in the pe.iod 2000-2008. Companies in Indonesia following the dvnahic capital structurc, thc targei compmy's capital struclure adjust over time and it is a lunclion ofexogenous and endogenous faclors change' ' Bas€d on the results ofthe analysis show thal lhe optimal leverase chang€s. arc siSnificanllv influencell by seleral faclrrsl NDTS (Non Debt T[\ Shield), IANG (TansibiliB), GROWTH, SIZE, PROF (Profitabilitv), TCS (Trade Credit to Sales), TDS (Trade D€b1 to Sales), TA-X, LIQ Giquiditv), and the optimal leverage fluctuale reflecb the company adiustment over time to exogenous elld e.doSenous facron of fim. The study also speci8 the speed of adjusbne,l towds the oplirnal level of levemge. The ^mounl of adjust enl of.he @mpeny i') achieving oplimal levemge on average per v@ of0.80 or 80% witlin one ver or ihe averag€ lime required to achieve the opdmai leveBgc is 1.26 yeJs.Speed of ad;justment aftbcted. bv lift charct ristics. Curent liab;lilies, 8roMh, and lhe size of tte companv showed a posifive efiect, while pmfitability shows a negative effelt ard that show signincant effect on the sp€ed ofadjustr.€nt is profitabiliry.